Acruliopsis gen. n. aus der Ostpaläarktis (Coleoptera, Staphylinidae, Omaliinae, Omaliini) (Beiträge zur Kenntnis ostpaläarktischer Insekten; 14). - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 2003)
The genus Acruliopsis gen. n. (type species: Acruliopsis watanabei sp. n.) is described, based on a phylogenetic analysis. Acruliopsis ussuriensis sp. n. (Russia: Primorskiy Kray) and Acruliopsis watanabei sp. n. (Japan: Honshû, Yamanashi-ken) are described and compared with the related species. Acruliopsis denticollis (Sharp, 1889) comb. n. and Acruliopsis nipponica (Watanabe, 1980) comb. n. are transferred from the genus Pycnoglypta Thomson, 1858. A key to species is provided.KeywordsColeoptera, Staphylinidae, Omaliinae, Omaliini, new genus, new species, redescriptions, phylogeny, key, Far East of Russia, Japan.Nomenclatural Actsdenticollis (Sharp, 1889) (Acruliopsis), comb. n. hitherto Omalium denticollenipponica (Watanabe, 1980) (Acruliopsis), comb. n. hitherto Pycnoglypta nipponicaussuriensis Zerche, 2003 (Acruliopsis), spec. n.watanabei Zerche, 2003 (Acruliopsis), spec. n.Acruliopsis Zerche, 2003 (Staphylinidae), gen. n.